Human-AI Collaboration in Food Delivery - Praveen Payili, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the implementation of artificial intelligence systems in food delivery platforms, focusing on online food ordering company's comprehensive integration of AI technologies across its operational framework. The article analyzes four key areas: communication safety through SafeChat+, voice ordering systems, advanced data engineering applications, and technical challenges with their solutions. The article demonstrates how AI integration has transformed food delivery operations through enhanced customer experience, improved operational efficiency, and sophisticated safety measures. The findings highlight the successful implementation of hybrid human-AI systems, showcasing significant improvements in order processing, delivery optimization, and customer service while addressing critical scaling, performance, and security challenges.
Keywords: Artificial Intelligence Integration; Food Delivery Platforms; Machine Learning Infrastructure; Voice Recognition Systems; Human-AI Collaboration